Children With Convulsive Epileptic Seizures Presenting to Padua Pediatric Emergency Department: The First Retrospective Population-Based Descriptive Study in an Italian Health District. (March 2015) - Bergamo, Silvia; Parata, Francesca; Nosadini, Margherita; Boniver, Clementina; Toldo, Irene; Suppiej, Agnese; Vecchi, Marilena; Amigoni, Angela; Da Dalt, Liviana; Zanconato, Stefania; Perilongo, Giorgio; Sartori, Stefano
Convulsive epileptic seizures in children represent a common cause of admission to pediatric emergency department. Data about incidence, etiology, and outcome are still lacking in literature. We retrospectively reviewed medical records of children presenting to our pediatric emergency department with convulsive seizures during a 12-month period and collected their diagnoses over the following year. In all, 182 children met the inclusion criteria, for a total of 214 visits (1.2% of all attendances, n = 24 864). Seizures lasted less than 5 minutes in 76%, 5 to 30 minutes in 20%, 30 to 60 minutes in 2%, and over 60 minutes in 2% visits ("early, " "established, " "refractory, " convulsive status epilepticus, respectively). Incidence of "early" (seizure lasting 5-30 minutes) and "established" (seizure lasting 30-60 minutes) status epilepticus was 52/100 000/year and 7/100 000/year respectively. Most common causes were febrile seizures (56%) and remote symptomatic seizures (19%). Knowing the epidemiology of convulsive seizures in children is important to guide appropriate management and individualized follow-up.